A Town Called Solace - Lawson, Mary (London Chatto & Windus, 2021)
"As Solace opens, we meet a Northern Ontario family in crisis: their rebellious teenage daughter, Rose, has disappeared. Weeks have passed with no word, but still Rose's little sister, Clara, keeps a daily vigil at the living-room window, hoping that Rose will come back. Feisty and fierce, Clara is not only missing Rose; she is also missing her elderly friend and next-door neighbour, Mrs. Orchard, a retired schoolteacher who is away in hospital. While standing at the window, Clara keeps an eye out for Rose and an eye on Mrs. Orchard's house. Then, one afternoon, a strange young man in a strange car pulls into Mrs. Orchard's driveway and proceeds to move into the house as if he owns the place. Which it turns out he does: Mrs. Orchard has died and left it to him. Soon we discover that Clara's beloved Mrs. Orchard has a complicated and tragic past, and the real mystery at the heart of this novel is what happened between her and Liam, the man in the car"